DISTRIBUTION OF MAMMALS OF THE BAHAMAS ... - Buden, Donaldw (Zenodo, 1986)
(Uploaded by Plazi for the Bat Literature Project) Excluding feral populations and failed introductions, 21 species of mammals are known from the Bahamas. Four (Pmcyon lotor, Rattus rattus, R . norvegicus, Mus musculus) are regarded as introduced, three (Lonchorhina aurita, Glossophaga soricina, Lasionycteris noctivagans) are accidental, and two (Pteronotus parnellii, Momoops blainvillii) are known in the Bahamas only as fossils. Of the 14 indigenous and presumably breeding resident (or formerly resident) species, one ( Geocapromys ingrahami) is a rodent and the others are bats. G. ingrahami and three subspecies of bats (Natalus micropus tumidifrons, Eptesicus fuscus bahamensis, Tadarida brasiliensis bahamensis) are endemic to the Bahamas. A t least 12 of tne 14 resident species probably reached the Bahamas from the Greater Antilles, and the two others probably either from the Antilles or from continental North America. Cuba appears to have contributed more breeding resident species (at least six) than has ...